Challenges facing international faculty at Japanese universities: Main findings from the 2017 national survey. (November 2019) - Huang, Futao; Daizen, Tsukasa; Kim, Yangson
Highlights: International faculty at Japanese universities showed general satisfaction with work and employment situations, and overall professional environment. Despite differences in degree, international faculty at Japanese universities believed that they experienced many challenges at national, institutional and personal levels. Especially the American and British junior faculty from the Humanities seem to encounter more difficulties such as unstable employment, uncertain career prospects and serious competitive survival situation than any other categories of international faculty. Abstract: The purpose of this study is to explore the main challenges facing full-time international faculty at Japanese universities based on relevant findings from a national survey of them which was carried out from June to August 2017. The study suggests that despite differences in degree, international faculty believed that they experienced many challenges at national, institutional and personal levels. This is especially true in the cases of their responses to the survey questions about the closed nature of Japanese academic market to international faculty and institutional atmosphere. Further, differences in their attitudes toward large numbers of survey questions by academic rank, discipline and nationality are noteworthy and extremely relevant as well. Finally, the American and British junior faculty from the Humanities seem to encounter more difficulties such as unstable employment, uncertain career prospects and serious competitive survival situation than any other categories of international faculty.